Effect of Oat flour on Quality Characteristics of Low-Fat Chicken Sausages - Reddy, G.V. Bhaskar; Kumar, M. Shashi; Gupta, R.S.D.; Kiran, M.; Reddy , K. Kondal (Journal of Meat Science, 2012)
This study was conducted to evaluate the influence of adding oat flour at various levels i.e. 3, 6 and 9 per cent on physico-chemical, proximate, textural and sensory attributes of low-fat chicken sausages as compared to 9 per cent ground nut oil control sausages. Significant (P < 0.05) improvements in cooking yield, emulsion stability, water-holding capacity, pH were noticed and low fat chicken sausages incorporated with 9 per cent oat flour had recorded significantly (P
Keywords: Low-fat chicken sausages; fat replacers; oat flour; quality characteristics